3D mixed convection MHD flow of GO-MoS2 hybrid nanoparticles in H2O–(CH2OH)2 hybrid base fluid under the effect of H2 bond. (January 2020) - Ghadikolaei, S.S.; Gholinia, M.
Abstract: In this achievement, the physical perspectives on 3D natural convection MHD flow of GO- MoS2 / Water (H2 O)-Ethylene glycol (C2 H6 O2 ) (50:50 Vol%) hybrid nanofluid under the effect of thermal ray, shape and slip factors has been presented using Runge- Kutta Fehlberg 5th order (RKF-5) numerical procedure. The infiltration of diverse parameters for instance: suction/ injection parameters, thermal radiation, and nanoparticle shapes (Cylinders, Platelets, and Bricks), on velocity and temperature profiles are exemplified qualitatively through graphs. Outputs indicate that: Lorentz force created by augmenting magnetic square parameter (M) causes diminution in the velocity profile. The radiation parameter has used to breakdown hydrogen bonds of fluid molecules. Additionally, strong hydrogen bonding of hybrid nanofluid (GO- MoS2 ) causes a sharp increase in thermal conductivity and, consequently, increment in temperature profile (H2 bond Hybrid ‐phase > H2 bondNano‐phase ). Increasing the shape factor has always increased temperature profile and heat transfer rate, so the number of hydrogen bonds also decreases. Highlights: A numerical study on the effect of H2 bond on free convection MHD flow of GO- MoS2 / Ethylene glycol-water hybrid nanofluid is done. The radiation parameter has used to breakdown hydrogen bonds of fluid molecules. The strong hydrogen bonding of hybrid nanofluid causes a remarkable increase in thermal conductivity. The Nusselt number has direct relation with the shape factor and has reverse relation with the number of hydrogen bonds.